Cloud Systems Used in Smart Agriculture, the Internet of Things and Uses of Other Technologies and a Smart Agriculture Architectural Proposal - Fatih Çağatay Baz (Turkish Journal of Agriculture: Food Science and Technology)
Agriculture has been important all over the world since the first days of humanity. The development of agriculture is proportional to the development of humanity. Today, people have reached the point they have reached in technology with agriculture. Today, the use of technology with different topics is effective in ensuring the development of agriculture. The concept of smart agriculture was born from here. The hardware and software used today provide convenience to manufacturers, production increases and businesses gain more profit. For this purpose, cloud systems, internet of things, artificial intelligence applications and many other technologies are used. In this study, it is focused on designing applications that can be used in smart agriculture in the light of current technologies, especially cloud systems and internet of things for producers. In addition, studies on smart agriculture in the literature were analysed by using the document analysis method. It has been determined that the studies on smart agriculture in the literature are similar. According to the research findings, applications related to smart agriculture aim to enable producers to obtain products with less cost. It can be suggested that manufacturers and experts working in the field of informatics work together to achieve this.